Desired Job Characteristics for Males and Females - Pyke, Sandra W.; Weisenberg, Faye P. (Canadian Journal of Counselling and Psychotherapy, 2012)
Herzberg, Mausner and Synderman (1959) have classified job characteristicsas either self-actualizing factors (motivators) or physical job features (hygienes). A sample of 42 professional and 46 non-professional men and women reported their order of preference for 10 job characteristics (5 motivators and 5 hygienes) and also indicated their perception of the importance of these job traits for male and female co-workers. Both sexes regarded motivators as personally more important than hygienes but non-professional respondents were significantly more concerned about hygienes than the professional group. Females, both professional and non-professional, did not perceive any significant differences between themselves and their male and female co-workers, while males rated themselves as significantly more influenced by motivators than they believed their female co-workers to be. Male and female non-professionals rated their male colleagues as more interested in the self-actualizing factors thantheir female co-workers. These results are discussed in terms of the possible negative consequences of the image of the less committed female worker.